ANALYSIS OF THE ANXIOLYTIC POTENTIAL OF NANOENCAPSULATED ESSENTIAL OIL OF OCIMUM GRATISSIMUM IN VALIDATED TESTS WITH RODENTS (CIPEEX, 2025)
INTRODUCTION: According to the World Health Organization (WHO), anxiety affects around 10% of the population in Brazil, impacting individuals not only through symptoms but also through the adverse effects of medications currently available in the pharmaceutical market. In light of this, therapeutic approaches using natural compounds have gained prominence. OBJECTIVE: This study aims to analyze the anxiolytic effects of nanoencapsulated essential oil and assess rodent behavior using the Open Field (OF) and Elevated Plus Maze (EPM) tests. METHODS: Male Swiss mice will be used in behavioral tests: the Open Field (OF) test to assess spontaneous locomotion and exploratory behavior, and the Elevated Plus Maze (EPM) to evaluate the amount of time spent and the number of entries into the open arms. RESULTS: The essential oil of Ocimum gratissimum, both in its nanoencapsulated and free form, will be tested in mice to analyze behavior and achieve key therapeutic advantages, such as increased stability, bioavailability, and controlled release of the active compound. Comparing both forms will reveal different behaviors among the rodents, allowing for a better understanding of their mechanisms of action. Furthermore, this research highlights Brazilian biodiversity and represents a more accessible, sustainable, and compatible therapeutic strategy for the needs of the public health system. CONCLUSION: The results propose an innovative approach to developing new therapies for the treatment of anxiety disorders by investigating the anxiolytic effects of nanoencapsulated Ocimum gratissimum essential oil. It is expected that the findings will contribute to the formulation of new phytotherapeutic agents, expanding more sustainable and humanized therapeutic options.